СТІЙКІСТЬ СИЛОВИХ КАБЕЛІВ В УМОВАХ ПОЖЕЖІ. КОМП'ЮТЕРНЕ ТА ЕКСПЕРИМЕНТАЛЬНЕ ДОСЛІДЖЕННЯ - Щерба, А.А.; Подольцев, О.Д.; Кучерява, І.М.; Розіскулов, С.С.; Білянін, Р.В.; Антонець, Т.Ю. (Інститут електродинаміки НАН України, Київ, 2025)
The work is dedicated to the experimental and numerical study of ways to increase the resource and reliability of power cables under fire emergency conditions. Firstly the computer model is developed and the temperature field in XLPE-insulated power cable operating at fire emergency is studied. The thermal processes in the case of the fireproof coating with different thickness located on the central section of the cable around it are analyzed. Two main factors of the additional coating are revealed: 1) the time of stable reliable operation of the cable at fire gradually increases with an increase in the thickness of the coating (a positive factor); 2) under normal operating conditions, due to cooling deterioration, the temperature of the insulation on the section of the cable, corresponding to the coating, increases with an increase in the thickness of the coating (a negative factor). Such factors should be taken into account when applying and choosing the dimensions of the coating. At the second stage of the work, the experimental study of power cable destruction under conditions close to a fire, i.e. under the direct influence of open flame, is carried out. The time from the beginning of the fire, during which the cable under the influence of the flame allows powering the load, is determined. References 17, figures 10.